Approaches for filtrate utilization from synthetic gypsum production; Environmental Science and Pollution Research (ESPR); Vol. 30, iss. 12 - Romanovski V. Valentin; Xintai Su; Lijuan Zhang; Paspelau A. Andrei; Smorokov A. A. Andrey Arkadievich; Sehat A. A. Ali Akbari; Akinwande A. A. Abayomi Adewale; Korob N. Natalia; Kamarou M. Maksim (2023, 2023)
Title screen